Religious e-Xpression among the Youths in the Indonesian Cyberspace - Leonard Epafras (Jurnal ILMU KOMUNIKASI, 2016)
Abstract: About eighty-two per cent of online Indonesians are younger generation. Online realm for this generation is a space for the quest of individuation, socialization, and of its piety. This research-based article investigates the religious expressions in this realm. The research adopted mixed methods including online survey. However, the data interpretation and the fi nal report remain qualitative. The fi nding suggested the complexity and multiple directions of religious expressions that also indicated the intersection of a number of issues such as the evasion of religious authority, conservatism, imagination of pluralistic society, and the transnational religious phenomenon.Abstrak: Sekitar 82 persen orang Indonesia yang aktif di internet adalah kaum muda. Dunia online bagi mereka adalah ruang untuk individualisasi, sosialisasi, dan ekspresi kesalehan. Makalah ini adalah penelisikan berdasarkan penelitian tentang ekspresi keagamaan di internet bagi generasi millenial. Penelitian ini mengadopsi metode campuran termasuk survei online. Namun, interpretasi data dan laporan akhir tetap bersifat kualitatif. Temuan penelitian menunjukkan kompleksitas dan beragamnya ekspresi keagamaan yang juga menunjukkan tumpang tindihnya isu seperti pengelakan terhadap otoritasagama, konservatisme, bayangan akan masyarakat majemuk, dan gejala keagamaan transnasional. Kata Kunci: ekspresi keagamaan, generasi millenial, internet Indonesia.